The Impact of Perceived Discrimination on Cultural Identification, Psychological Stress, Emotion Regulation and Aggressive Tendencies in Individuals With Turkish Migration Background in Germany - Dingoyan, Demet; Metzner, Franka; Kongur, Akin; Arslan, Örsan; Pust, Gesa Elena Albertine; Weierstall-Pust, Roland (Frontiers in Sociology, 2022)
The following study considers correlates of the identification with the origin and host culture of German individuals with a Turkish migrant background. It examines how these two factors mediate the relationship between perceived discrimination, emotion regulation or psychological stress, and aggressive tendencies as the major dependent variable. For this purpose, the data of 229 people with Turkish migration background living in Germany was collected through an online survey. Findings depict that the identification with the Turkish (origin) and German (host) culture mediate the relationship between perceived discrimination and emotion regulation. The relationship between perceived discrimination and psychological stress is mediated by the identification with the German culture. The analysis shows that perceived discrimination is associated with a reduced identification with the German culture and with a high identification with the Turkish culture. Emotion regulation abilities are negatively related to perceived discrimination and identification with the Turkish culture. In contrary, the psychological stress level is positively related to perceived discrimination. The preparedness for aggressive behavior is also associated positively by psychological stress and negatively by emotion regulation abilities. The results are discussed against the background of the specific migration history and living conditions of Turkish immigrants in Germany.